Primum non nocere. The SARS-CoV-2 pandemic course in oldest - Cucinotta, Domenico (Acta Biomedica Atenei Parmensis, 2020)
Dramatic outcomes of Covid-19 pandemia in Italy, in particular in the North, must be discussed. Maybe a bad strategy and lack of timely intervention togheter with concurrent social events, comorbidities of oldest persons, bed rest, inadequate nutritional support and drugs’ side effects and infection of health professionals proved fatal for many.